Psychological and Physiological Motives in Humans (Study on Verses of The Qur'an) - Murjazin, Murjazin; Nurhuda, Abid; Susanti, Linna; Azami, Yasin Syafii (Universitas Muhammadiyah Surakarta, 2023)
The Al-Qur'an is the official guideline and is an interesting material for Muslims to study because it is comprehensive about all aspects of life. This is proven, one of which is with several verses that explore the nature of human creation to the deviations it commits. So guidance, coaching, education, and healing are needed both from the psychological and physiological aspects. So the purpose of this study is to describe the Psychological and Physiological Motives in Humans (Studies on the Verses of the Qur'an). The method used is literature in the process of collecting data, then careful analysis is carried out, and finally, descriptive conclusions are drawn. The results of the study show that the physiological motives in the Qur'an are divided into two parts, namely the motive for being oneself and the motive for preserving offspring. While the psychological motives are divided into four parts, namely ownership motives, competition motives, hostility motives, and religious motives. These two things show how the Qur'an pays great attention to various kinds of matters including the different human souls and physiques so that it not only exhibits various kinds of heavenly pleasures and the pain of the torments of hell but also provides insight for humans regarding this matter things that are useful for their daily life.